(untitled) (Journal of the College of Basic Education, 2022)
A new heterocyclic compounds(II-V)were synthesized through a reaction of compound(I) with urea,thiourea,hydrazine hydrate, and hydroxylamine hydrochloride and series of Schiff bases(VIa-d) and (VIIa-d) were synthesized from( II) and (III).The prepared compounds were characterized by (FT-IR) spectrum. Physical properties of the prepared compounds were recorded and their mesomorphic phases were investigated.